IMAGE OF PERSON IN 19TH CENTURY TOMBSTONE EPITAPHS FOUND IN VILNIUS CEMETERIES: DIMENSION OF COMMUNICATION - TOLKAČEVSKI, KŠIŠTOF (Knygotyra, 2013)
Epitaph as a research source has attracted the attention of historians, art historians, architects, linguists, etc. All these scientists usually investigate epitaph within their field of interest. However, semantic interpretation of an epitaph’s text enables us to gain more insights into its nature. An epitaph can be considered in the context of the Communication Sciences as a communication tool because it conveys a certain message. Its primary purpose was to perpetuate and glorify the deceased by naming his/her virtues. It provides great opportunity to reconstruct not only the image of the person that lived in the period explored by using the features named. Furthermore, by reconstructing the social context of the person described in the epitaph we can better understand broader social-political settings of that time. Secondly, despite the fact that in the course of time an epitaph had slightly changed its structure and content, the purpose of devotion remained. In the text of the epitaph, a passer-by was asked politely in the name of a buried man to pray for his/her soul. The tradition to believe that prayers could relieve the suffering of a soul in purgatory and reach salvation was widely spread in the 14th–19th centuries. Last but not least, epitaphs were supposed to make an impact on the younger generation by presenting the virtues of a deceased man, inscribed in the text on the tomb.The last objective makes epitaph an exclusive means of communication, as in a certain region or in a particular society it becomes a carrier of information from one generation to the next. The text written (encoded) by one generation with the code that is used in a restricted area (e.g., the dates or shortenings, important for that region, etc.) is decoded by the next generation. The conveyed message was intended to instill and foster the values in the new generation. Due to all the above mentioned purposes of an epitaph, it can be called a multi-message.The 19th century is important in the history of the European cemeteries, as it was a period of massive establishment of cemetery sites outside the cities. As a result, solid monuments were built, with epitaphs inscribed on them. From then onwards not only the nobles were those who could afford to build an epitaph, but local citizens as well. Many of these tombstones from the nineteenth century have survived to the present day. Therefore, epitaphs of the 19 th century are a great source revealing the image of the 19th century townsman. The main virtues that dominate in the texts of epitaphs, are related to being the patriot, who defends the Native land and responsibly fulfills his/her duties. One of the most important duties was to care for the family. In spite of the fact that the texts of epitaphs in the nineteenth century were copied on a mass scale, in many ways they preserved their exceptionality. However, the texts of epitaphs should be treated with responsibility, as in many cases epitaphs show the image of an ideal man.
Keywords: ...